Glycemic index, glycemic load and invasive breast cancer incidence in postmenopausal women: The PREDIMED study. Issue 6 (November 2016) - Castro-Quezada, Itandehui; Sánchez-Villegas, Almudena; Martínez-González, Miguel Á.; Salas-Salvadó, Jordi; Corella, Dolores; Estruch, Ramón; Schröder, Helmut; Álvarez-Pérez, Jacqueline; Ruiz-López, María D.; Artacho, Reyes; Ros, Emilio; Bulló, Mónica; et al.
Abstract : The objective of this study was to evaluate the prospective associations between dietary glycemic index (GI) and glycemic load (GL) and the risk for invasive breast cancer incidence in postmenopausal women at high cardiovascular disease (CVD) risk. This study was conducted within the framework of the PREvención con DIeta MEDiterránea (PREDIMED) study, a nutritional intervention trial for primary cardiovascular prevention. We included 4010 women aged between 60 and 80 years who were initially free from breast cancer but at high risk for CVD disease. Dietary information was collected using a validated 137-item food frequency questionnaire. We assigned GI values using the International Tables of GI and GL values. Cases were ascertained through yearly consultation of medical records and through consultation of the National Death Index. Only cases confirmed by results from cytology tests or histological evaluation were included. We estimated multivariable-adjusted hazard ratios for invasive breast cancer risk across tertiles of energy-adjusted dietary GI/GL using Cox regression models. We repeated our analyses using yearly repeated measures of GI/GL intakes. No associations were found between baseline dietary GI/GL and invasive breast cancer incidence. The multivariable hazard ratio and 95% confidence interval (CI) for the top tertile of dietary GI was 1.02 (95% CI: 0.42–2.46) and for dietary GL was 1.00 (95% CI: 0.44–2.30) when compared with the bottom tertile. Repeated-measures analyses yielded similar results. In sensitivity analyses, no significant associations were observed for women with obesity or diabetes. Dietary GI and GL did not appear to be associated with an increased risk for invasive breast cancer in postmenopausal women at high CVD risk.